Optimizing The Profit of Tartar Cake’s Slice Cakes Using Simplex Method - Vivian Bongso; Angela Velisca; Sheren Patricia; Sintia Juliawati Lestari; Dudy Effendy (Universitas Negeri Makassar, 2024)
This research was taken from a business operating in the food and beverage industry located in the Pontianak area, West Kalimantan, precisely on Jalan Hijas, namely